Auditing Board of supreme audit for solid waste management (Journal of Accounting and Financial Studies ( JAFS ), 2010)
Solid waste is considered to be one of the rescuers of pollution in case of     neglecting conditions and procedures relating to specific processes of laws, systems, and contracts requirements in addition to recommendations of organizations concerned with environment issue. The environments auditing groups of intosai have taking into account the environments control by various conference and recommended that the Board of supreme audit have and environments controlling taking into consideration auditing procedures on waste management ,and also offered on evidences for experiences of members of countries in order to exchange their knowledge's and experiments .the definition of solid waste and their resources ,risks ,management steps ,international contract and some experiences of various  countries have been outlined in the theoretical framework of this research on the other hand ,the empirical side is concern treated on the experiences of in environmental auditing related solid waste .the result of environments survey for municipalities by the central statistical organization .the researcher presents an auditing  program project for solid waste management. The research ended by some conclusions and recommendation.